Postural assessment of school children : an input for the design of furniture - Gonçalves, Maria Antónia (2012)
During the last decades of the previous century, school desks with a tilt top have disappeared. The chairs have been designed for sitting upright, with the hip, knees and ankles all at right angles. However, the erect posture cannot be maintained for more than one or two minutes, after which it will result in fatigue, discomfort or poor posture. The main aim of project is to identify the type of furniture that most effectively contribute to adequate neck and back postures of the school children, by carrying out a postural analysis of a sample of school pupils when using three different types of furniture. The postures adopted by school pupils were monitored by video during several activities, such as reading, writing and painting tasks, copying from a blackboard and listening the teacher. Additionally, the characteristics of the adopted postures were assessed by registering the head tilt, flexion of the neck, trunk and hips position. All these aspects were classified and the results were recorded for future analysis. The obtained results seem to point out that the use of a school desk with a tilted table surface resulted in a reduction in trunk and neck flexion, preserving the natural lordosis in the lumbar and cervical regions. Accordingly, it can be concluded that there are alternatives to consider in the furniture design in order to eliminate tensions and, consequently, to improve children’s wellbeing.